Fundamentals of inflammation - Serhan, Charles N.; Ward, Peter A., 1934-; Gilroy, Derek W. (Cambridge : Cambridge University Press, 2010)
'The acute inflammatory response is the body's first system of alarm signals that are directed toward containment and elimination of microbial invaders. Uncontrolled inflammation has emerged as a pathophysiologic basis for many widely occurring diseases in the general population that were not initially known to be linked to the inflammatory response, including cardiovascular disease, asthma, arthritis, and cancer. To better manage treatment, diagnosis, and prevention of these wide-ranging diseases, multidisciplinary research efforts are underway in both academic and industry settings. The purpose of this book is to provide an introduction to the cell types, chemical mediators, and general mechanisms of the host's first response to invasion. World-class experts from institutions around the world have written chapters for this introductory text. The text is presented as an introductory springboard for graduate students, postdoctoral Fellows, medical scientists, and researchers from other disciplines who wish to gain an appreciation and working knowledge of current cellular and molecular mechanisms fundamental to inflammation'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Inflammation